Long-term follow-up of patients with poor-risk acute leukemia treated on a phase 2 trial undergoing intensified conditioning regimen prior to allogeneic hematopoietic cell transplantation. Issue 5 (16th April 2022) - Salhotra, Amandeep; Yang, Dongyun; Mokhtari, Sally; Hui, Susanta; Al Malki, Monzr M.; Armenian, Saro; Sigala, Brianna; Aldoss, Ibrahim; Pullarkat, Vinod; Forman, Stephen; Marcucci, Guido; Nakamura, Ryotaro; et al.
Abstract: Patients with acute leukemia who undergo allogenic hematopoietic cell transplantation with active disease have high rates of relapse and poor overall survival (OS) post-transplant compared to patients undergoing HCT in remission. Here, we report the long-term outcomes in 32 patients who received a high-intensity conditioning regimen comprising fractionated total body irradiation (FTBI; 1200 cGy) with pharmacokinetic (PK) dosing of intravenous Busulfan (IV BU) targeted to first dose area under curve (AUC) of 700–900 µM/min and etoposide (30 mg/kg) in a prospective phase 2 clinical trial. The median age of the patients at the time of HCT was 37 years (range: 18–50) presenting with high-risk ( n = 6) and relapsed/refractory(r/r) acute leukemias ( n = 26). All but one patient underwent HCT using peripheral blood stem cells from matched sibling donors. At a median follow-up of 17.3 years (range 14.4–19.0), 11 patients remained alive. The disease-free survival and OS at 15 years was 34% (versus 40% at 5-years post-HCT). The 15-year cumulative incidence of relapse was 26% and non-relapse mortality (NRM) was 38% (95% CI: 21–54%) and the cumulative incidence of chronic GVHD at 15 years was 33% using a prophylactic regimen of cyclosporine A and mycophenolate mofetil. The most common life-threatening late effects were secondary malignancies, metabolic, or cardiac complications with a cumulative incidence of 6.6%, 6.6%, and 13.3%, respectively. No unusual late effects or patterns of relapse were noted on longer followed on patients treated with intensified myeloablative condition regimen. Results from this study supports continued development of intensive conditioning regimens in patients with r/r acute leukemias to improve leukemia free (LFS) and OS in this high-risk population.